Autonomic Dysfunction in α-Synucleinopathies - Mendoza-Velásquez, José Javier; Flores-Vázquez, Juan Francisco; Barrón-Velázquez, Evalinda; Sosa-Ortiz, Ana Luisa; Illigens, Ben-Min Woo; Siepmann, Timo (Frontiers in Neurology, 2019)
The α-synucleinopathies are a group of neurodegenerative diseases characterized by abnormal accumulation of insoluble α-synuclein in neurons and glial cells, comprising Parkinson's disease (PD), dementia with Lewy bodies (DLB) and multiple system atrophy (MSA). Although varying in prevalence, symptom patterns, and severity among disorders, all α-synucleinopathies have in common autonomic nervous system dysfunctions, which reduce quality of life. Frequent symptoms among α-synucleinopathies include constipation, urinary and sexual dysfunction, and cardiovascular autonomic symptoms such as orthostatic hypotension, supine hypertension, and reduced heart rate variability. Symptoms due to autonomic dysfunction can appear before motor symptom onset, particularly in MSA and PD, hence, detection and quantitative analysis of these symptoms can enable early diagnosis and initiation of treatment, as well as identification of at-risk populations. While patients with PD, DLB and MSA show both central and peripheral nervous system involvement of α-synuclein pathology, pure autonomic failure (PAF) is a condition characterized by generalized dysregulation of the autonomic nervous system with neuronal cytoplasmic α-synuclein inclusions in the peripheral autonomic small nerve fibers. Patients with PAF often present with orthostatic hypotension, reduced heart rate variability, anhydrosis, erectile dysfunction, and constipation, without motor or cognitive impairment. These patients also have an increased risk of developing an α-synucleinopathy with central involvement, such as PD, DLB or MSA in later life, possibly indicating a pathophysiological disease continuum. Pathophysiological aspects, as well as developments in diagnosing and treating dysautonomic symptoms in patients with α-synucleinopathies are discussed in this review.